Hexose monophosphate shunt, the role of its metabolites and associated disorders: A review. Issue 9 (29th January 2019) - Akram, Muhammad; Ali Shah, Syed Muhammad; Munir, Naveed; Daniyal, Muhammad; Tahir, Imtiaz Mahmood; Mahmood, Zahed; Irshad, Muhammad; Akhlaq, Muhammad; Sultana, Sabira; Zainab, Rida
Abstract: The hexose monophosphate (HMP) shunt acts as an essential component of cellular metabolism in maintaining carbon homeostasis. The HMP shunt comprises two phases viz. oxidative and nonoxidative, which provide different intermediates for the synthesis of biomolecules like nucleotides, DNA, RNA, amino acids, and so forth; reducing molecules for anabolism and detoxifying the reactive oxygen species during oxidative stress. The HMP shunt is significantly important in the liver, adipose tissue, erythrocytes, adrenal glands, lactating mammary glands and testes. We have researched the articles related to the HMP pathway, its metabolites and disorders related to its metabolic abnormalities. The literature for this paper was taken typically from a personal database, the Cochrane database of systemic reviews, PubMed publications, biochemistry textbooks, and electronic journals uptil date on the hexose monophosphate shunt. The HMP shunt is a tightly controlled metabolic pathway, which is also interconnected with other metabolic pathways in the body like glycolysis, gluconeogenesis, and glucuronic acid depending upon the metabolic needs of the body and depending upon the biochemical demand. The HMP shunt plays a significant role in NADPH2 formation and in pentose sugars that are biosynthetic precursors of nucleic acids and amino acids. Cells can be protected from highly reactive oxygen species by NADPH 2 . Deficiency in the hexose monophosphate pathway is linked to numerous disorders. Furthermore, it was also reported that this metabolic pathway could act as a therapeutic target to treat different types of cancers, so treatments at the molecular level could be planned by limiting the synthesis of biomolecules required for proliferating cells provided by the HMP shunt, hence, more experiments still could be carried out to find additional discoveries.